2010
DOI: 10.1080/13545701.2010.508574
|View full text |Cite
|
Sign up to set email alerts
|

Working Long Hours and Having No Choice: Time Poverty in Guinea

Abstract: This contribution provides a new definition of time poverty as working long hours without choice because an individual's household is poor or would be at risk of falling into poverty if the individual reduced her working hours below a certain time-poverty line. Time poverty is thus understood as the lack of enough time for rest and leisure after accounting for the time that has to be spent working, whether in the labor market, doing domestic work, or performing other activities such as fetching water and wood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 17 publications
0
81
1
2
Order By: Relevance
“…Therefore, the actual time daily spent on biogas production might be more important than the other benefits of biogas. Moreover, spending additional time on biogas production can pose significant problems, especially for rural women who are already strapped for time (i.e., below time poverty line) [1,2,53]. Ignoring the importance of time for its operation and focusing on the general benefits, namely on reduction of indoor air pollution, deforestation, and its slurry use alone, may not help in the adoption and use of the technology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the actual time daily spent on biogas production might be more important than the other benefits of biogas. Moreover, spending additional time on biogas production can pose significant problems, especially for rural women who are already strapped for time (i.e., below time poverty line) [1,2,53]. Ignoring the importance of time for its operation and focusing on the general benefits, namely on reduction of indoor air pollution, deforestation, and its slurry use alone, may not help in the adoption and use of the technology.…”
Section: Discussionmentioning
confidence: 99%
“…Various analyses of time-use data have demonstrated that women and men living in income-poor households spend more time in unpaid work than in nonpoor households, given that poverty is associated with lack of infrastructure and limited access to care services, frequently leading to overwork (Budlender 2008;Hirway 2010a). Time-use data can show the time-related constraints of the poor in terms of both time stress (overwork) and time allocation, thus informing the provision and allocation of public infrastructure (Elena Bardasi and Quentin Wodon 2010;Hirway 2010a). Time-use data has also been used to evaluate poverty alleviation policies that impose conditions on women (usually, that children attend school and healthcare check-ups) in exchange for cash transfers, indicating that these time costs are nontrivial and in some cases might offset transferred income (Sarah Gammage 2010).…”
Section: Broadening the Policy Agendamentioning
confidence: 97%
“…Overall, women put considerably more time toward household sustenance (chores and fetching firewood and water) and direct care. Time-use studies from other parts of sub-Saharan Africa also point to the stark gender inequality in the division of labor where household work is mainly women's responsibility with very little assistance from men (Bardasi & Wodon, 2010;Karamba & Winters, 2015;Pitcher, 1996). 5 Household size and composition, and infrastructure are other factors that may exacerbate the overall work burden.…”
Section: F I G U R E 1 Division Of Awake Time Across Gender and Activmentioning
confidence: 99%
“…Difficulties in assigning a monetary value to household activities such as cleaning, cooking, and care work group discussions and interviews conducted in 2013 in the Nampula region suggest that most smallholders are constrained by seed availability and other inputs required for cultivating the land. 11 Data from time-use surveys suggests that men usually have substantial more leisure time than women (Bardasi & Wodon, 2010;Arora, 2015). We, therefore, assume endogenous productivity only for the woman as she is more likely to be time-poor compared to the man and to experience falling labor productivity due to excessive workload.…”
Section: =̄+mentioning
confidence: 99%
See 1 more Smart Citation